Sistem Pendingin Otomatis dan Monitoring Suhu pada Panel Box Recloser Menggunakan Sensor MLX90614 Berbasis ESP8266 - I Dewa Gede Dodi Pranata; I Gusti Alit Wiraguna Jaya; Made Ary Wiradhi Putra; I Gede Suputra Widharma; I Ketut Darminta; I Gede Nyoman Sangka; Anak Agung Ngurah Gde Sapteka (LPPM STIKI MALANG, 2022)
The need for reliable tools or machines has become a priority for everyone today, from tools used for personal use to tools or machines used for industry. State Electricity Enterprise (PLN) also needs reliable tools to monitor assets with high accuracy. One of the components to monitor the load on the network is a recloser. This component is often disconnected from the dispatcher control center so that it cannot be monitored. One of the causes of the disconnection between the recloser device and the control center is the occurrence of excessive heat in the recloser box panel which causes the components inside to overheat. The automatic cooling system in the recloser panel box aims to maintain the temperature inside the panel box to be able to provide maximum component performance. In this study, an application was developed that was able to monitor temperature readings in the recloser panel box and monitor the condition of the cooling system inside. From the test results, it is known that the temperature conditions inside the panel box are monitored to be stable, even though outside the panel box there is an excessive temperature spike.